Komunikasi Transendental Manusia-Tuhan - Wahidah Suryani Djafar (Farabi, 2015)
Communication as the process of delivering a message from the communicator to communicant through media and produce effect, raises questions related to human communication made with God by naked eye can not see. This paper discusses the transcendental communication, ie communication that occurs between man and God. In this paper stated that all communication elements exist in communication between man and God. Source of communication or communicators consisted of God and man. The message in the form of verses of God through the Qur’an and pray, remembrance delivered man to God. The line is the Qur'an serve as channels of God's messages and intra channel's private. Receiver or communicant basically the same as the source or communicator. And feedback effects expected in this transcendental communication is a human being should do what he was told and stay away from what is forbidden. Effects can also be granted the praying, inner peace, or can occupy heaven in the hereafter. While the models of communication that could be in line with the communication process is the Model SR transcendental, Aristotle Model, and Model of Lasswell.